2016
DOI: 10.1136/archdischild-2016-311053
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated intravascular coagulation in paediatrics

Abstract: Disseminated intravascular coagulation (DIC) in paediatrics is associated with significant morbidity and mortality. Although there have been several recent advances in the pathophysiology of DIC, most of these studies were done in adults. Since the haemostatic system is very different in early life and changes dramatically with age, creating a variety of challenges for the clinician, delay in the diagnosis of DIC can happen until overt DIC is evident. In this review article, we report the aetiology, pathophysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 30 publications
2
42
0
7
Order By: Relevance
“…Infection was the most common underlying conditions in both ODIC and NDIC groups, followed by organ failure and malignancies, respectively. That result was the same as the previous study in children by Oren et al however, the percentage of subjects with DIC in that study was high as 95% . The previous studies by Chuansumrit et al showed that congenital abnormality of cardiovascular and gastrointestinal systems were the common underlying conditions of DIC in Thai children.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Infection was the most common underlying conditions in both ODIC and NDIC groups, followed by organ failure and malignancies, respectively. That result was the same as the previous study in children by Oren et al however, the percentage of subjects with DIC in that study was high as 95% . The previous studies by Chuansumrit et al showed that congenital abnormality of cardiovascular and gastrointestinal systems were the common underlying conditions of DIC in Thai children.…”
Section: Discussionsupporting
confidence: 87%
“…That result was the same as the previous study in children by Oren et al however, the percentage of subjects with DIC in that study was high as 95%. 15,28 The previous studies by 31 Mortality gradually increased with the increment of total ISTH DIC score in this study which was the same as previous study by Voves et al 32 The bleeding and thrombotic events in this study also increased with the increment of total ISTH DIC score. Those findings were similar to the previous study in children with acute promyelocytic leukemia which showed significantly higher coagulopathy-related adverse events but the sensitivity and specificity were not good at 66%-67%.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the multiple logistic regression analysis revealed that birth weight and gestational age were independently associated with in-hospital death. Previous reports have shown that the mean levels of many coagulation and anticoagulation factors were significantly lower in preterm than in term infants [3,18,19], and that differences resulting from the immaturity of organ function in preterm infants led to coagulopathy. Those reports are in line with the findings of this study and indicate that neonatologists should carefully evaluate the coagulation status of preterm infants.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely described in pediatric and neonatal populations, but there are few clinical studies that report its incidence and prognosis in these populations worldwide because of the difficulty of diagnostic testing [1]. We used the specific guidelines and diagnostic criteria for neonatal DIC [2][3][4]. Neonatologists in Japan diagnose neonatal DIC according to these specific diagnostic criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in the pediatric population, the difficulty in obtaining frequent blood tests due to low blood volume, the confounding factor of normal and abnormal ranges in the different age groups, and uncommon requests for fibrinogen levels and almost never requested D-dimers means that DIC diagnosis will only be sustained in the most dramatic cases. 55 A recent international survey (LimeSurvey software) published under the auspices of the ISTH working groups of pediatrics and DIC noted variable practices among pediatricians who diagnose and manage DIC. 56 At least half of respondents would use their own personal clinical experience to diagnose DIC; while one-third followed the ISTH guideline, many followed an institutional protocol.…”
Section: Is Disseminated Intravascular Coagulation Uncommon In Pediatmentioning
confidence: 99%